Cancer Stem Cells and their Management in Cancer Therapy - Shenouda, Suzan; Kulkarni, Ketan; Abuetabh, Yasser; Sergi, Consolato (Recent Patents on Anti-Cancer Drug Discovery, 2020)
Background: In the last decade, the proposed Cancer Stem Cell (CSC) hypothesis has steadily changed the way cancer treatment is approached. CSCs may be the source of the heterogeneous non-tumorigenic cell population included in a neoplasm. Intratumor and intertumoral heterogeneity is a well-known phenomenon that massively entangles the diagnosis and treatment of cancer. The literature seems to suggest that heterogeneity develops progressively within tumor-initiating stem cells. CSCs harbor genetic and/or epigenetic alterations that allow them to differentiate into multiple tumor cell types sequentially. Objective: The CSC hypothesis, cellular therapy, and the most recent patents on CSCs were reviewed. Methods: PubMed, Scopus, and Google Scholar were screened for this information. Also, an analysis of the most recent data targeting CSCs in pediatric cancer developed at two Canadian institutions is provided. The genes involved with the activation of CSCs and the drugs used to antagonize them are also highlighted. Results: It is underlined that (1) CSCs possess stem cell-like properties, including the ability for self-renewal; (2) CSCs can start carcinogenesis and are responsible for tumor recurrence after treatment; (3) Although some limitations have been raised, which may oppose the CSC hypothesis, cancer progression and metastasis have been recognized to be caused by CSCs. Conclusion: The significant roles of cell therapy may include an auto-transplant with high-dose treatment, an improvement of the immune function, creation of chimeric antigen receptor T cells, and the recruitment of NK cell-based immunotherapy.
Keywords: stem cells